ACTN-3 and ACE genotypes in elite male Italian athletes - Massidda, Myosotis; Corrias, Laura; Scorcu, Marco; Vona, Giuseppe; Calò, Maria Carla (Anthropological Review, 2012)
The ACE I/D and the ACTN-3 R577X polymorphisms are the most studied genes associated with elite athlete status, even if this association has been often conflicting. The aim of the present study was to investigate the association between the ACE and the ACTN3 genotypes and elite performance in Italian male athletes. The ACTN-3 R577X and the ACE I/D genotype distributions of 59 elite male Italian athletes practicing gymnastics (G; n = 17), 100 m–400 m running (R; n = 12), and playing soccer (S; n= 30) were compared with controls from Italian (C; n = 31) populations. For ACE distribution, athletes did not differ from controls (G, χ2 = 0.37, df = 2, p = 0.82; R, χ2 = 1.90, df = 2, p = 0.45; S, χ2 = 1.48, df = 2, p = 0.47) and the DD genotype was at very high frequency in all groups (G = 53%, R= 50%, S = 60%, C = 45%). For ACTN-3 distribution, elite gymnasts showed a significant difference from controls (χ2 = 6.57, df = 2, p = 0.03), showing an absence of XX genotype. Soccer players and runners did not differ from controls in ACTN-3 genotype distribution (R, χ2 =0.43, df = 2, p = 0.80; S, χ2 = 1.25, df = 2, p = 0.53). Even if the ACE DD genotype is often positively associated with elite sprint/power athlete status, its high frequency in Italian populations eliminates the possibility of its exclusive association in Italian athletes. The results of ACTN3 genotypes suggest that RR genotype of ACTN-3 gene is a determinant of elite gymnasts status but it is not the key factor for achieving a top-level performance in soccer or track events.